2012
DOI: 10.1016/j.ajo.2011.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Delayed- Versus Acute-Onset Endophthalmitis After Cataract Surgery

Abstract: Purpose To report a large consecutive case series of patients who developed delayed-onset and acute-onset endophthalmitis after cataract surgery. Design Retrospective consecutive case series. Methods The current study is a retrospective consecutive case series of patients treated between January 2000 and December 2009 for culture-proven endophthalmitis after cataract surgery. The study defined two groups after cataract surgery: acute-onset endophthalmitis (≤ 6 weeks after surgery) and delayed-onset endopht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 18 publications
2
102
1
1
Order By: Relevance
“…Shirodkar et al reported that recurrence of the infectious process in cases of delayed-onset endophtahlmitis is significantly decreased with pars plana vitrectomy, capsulectomy, and intraocular lens removal because of the removal of indolent organisms that remain in the capsular bag and on the intraocular lens. [16] The Achromobacter species have been shown to create a biofilm to survive otherwise toxic environments. [17] To our knowledge, this is the first report that shows histopathologic evidence of A. xylosoxidans on the lens capsule.…”
Section: Discussionmentioning
confidence: 99%
“…Shirodkar et al reported that recurrence of the infectious process in cases of delayed-onset endophtahlmitis is significantly decreased with pars plana vitrectomy, capsulectomy, and intraocular lens removal because of the removal of indolent organisms that remain in the capsular bag and on the intraocular lens. [16] The Achromobacter species have been shown to create a biofilm to survive otherwise toxic environments. [17] To our knowledge, this is the first report that shows histopathologic evidence of A. xylosoxidans on the lens capsule.…”
Section: Discussionmentioning
confidence: 99%
“…1 Chronic or delayed-onset endophthalmitis typically presents 6 weeks to months after cataract surgery, and isolated organisms are often found to be less virulent bacteria such as Propionibacterium acnes or fungal pathogens, although some species of Gram-positive and Gramnegative bacteria have been found. 2,3 The majority of patients with delayed-onset endophthalmitis present with plaque in the capsular bag, and often vitrectomy surgery with injection of antimicrobial medication into the capsular bag with or without removal of the intraocular lens seems to be curative. 2,3 Although our patient presented at 1 month, the clinical features more closely resemble those of delayed-onset or chronic endophthalmitis as opposed to acute endophthalmitis where, on average, cases present with more profound eye pain, redness, and purulent inflammation within the first postoperative week.…”
Section: Discussionmentioning
confidence: 99%
“…In one study with 118 patients, post-treatment acuity of 20/40 or better was present in 50 % of CPOE patients and only 27 % of APOE patients. However, 89 % of those with APOE had a presenting visual acuity of 5/200 or worse, a far greater percentage than the 31 % of those with CPOE with 5/200 or worse visual acuity [13]. …”
Section: Introductionmentioning
confidence: 99%